Kebahagiaan Spiritual dalam Komunikasi Parenting - mauludi, mauludi (Sekolah Ilmu Dakwah dan Komunikasi Islam (STIDKI) Ar Rahmah, 2024)
character, morality, and spirituality. In the context of Islamic da’wah, the family represents the most fundamental arena where Islamic values are instilled through exemplary behavior and compassionate communication. This study aims to analyze KH. Muhammad Shaleh Drehem’s concept of Da’wah Parenting as an Islamic parenting model that integrates the principles of mindful parenting and persuasive communication in nurturing a harmonious (sakinah) family. This research employed a qualitative descriptive method. Data were collected through in-depth interviews with KH. Muhammad Shaleh Drehem and his family, as well as discourse analysis of his lecture videos broadcast on Al-Irsyad TV. Data analysis was conducted using a constructivist approach and the Gioia method to identify thematic patterns and uncover the meaning of da’wah practices within his parenting approach. The findings reveal that KH. Muhammad emphasizes both parental self-awareness (intrapersonal awareness) and relational awareness toward children (interpersonal awareness) as the foundation of effective parenting. The core values identified include empathetic listening, non-judgmental acceptance, reduced impulsive reactions, and gentle persuasive communication. He places love, compassion, and exemplary conduct at the heart of family da’wah, viewing every child as a divine trust and chosen gift from Allah that must be nurtured with spiritual responsibility.This study contributes to the development of an integrative family-based da’wah model that bridges modern psychological insights with Islamic values, offering a renewed paradigm for family education—one that is grounded in mindfulness, compassion, and exemplary leadership..